2015
DOI: 10.1021/jacs.5b07883
|View full text |Cite
|
Sign up to set email alerts
|

Li-Filled, B-Substituted Carbon Clathrates

Abstract: Inside the cages of hypothetical carbon clathrates there is precious little room, even for the smallest atoms, such as Li-unless it is the Li(+) ion that is inserted, in which case a compensating negative charge should be distributed over the carbon cage. The hypothesis explored in this paper is that Li insertion can be achieved with appropriate B substitution within the framework. The resulting structures of 2Li@C10B2 (Clathrate VII), 8Li@C38B8 (Clathrate I), 7Li@C33B7 (Clathrate IV), 6Li@C28B6 (Clathrate H),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 121 publications
2
49
0
Order By: Relevance
“…In addition, all five carbon clathrates display a semiconducting electronic structure. Li doping of the B-substituted carbon clathrates reduced the band gaps of the carbon clathrate compounds to the range of 0.6 to 2.9 eV [21].…”
Section: Hybrid Carbon-nitrogen Clathratesmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, all five carbon clathrates display a semiconducting electronic structure. Li doping of the B-substituted carbon clathrates reduced the band gaps of the carbon clathrate compounds to the range of 0.6 to 2.9 eV [21].…”
Section: Hybrid Carbon-nitrogen Clathratesmentioning
confidence: 98%
“…Several energetically competitive structures, however, exist for each clathrate type. These authors concluded that B substitution stabilizes the cage structure and substantially lowers the energy cost for inserting Li atoms into the clathrate cages to about −2eV/Li at 1 atm pressure [21]. In addition, all five carbon clathrates display a semiconducting electronic structure.…”
Section: Hybrid Carbon-nitrogen Clathratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using VASP [19], Zeng et al [21] computed the energy of formation and band gaps for five different Li-filled, B-substituted carbon clathrates, including Li8C38B8 (Type I), Li6C28B6 (Type II), Li7C33B7 (Type IV), Li2C10B2 (Type VII), and Li6C28B6 (Type H) at the ground state. A range of strategies has been utilized to determine the energetics of replacing selected carbon atoms on the framework with boron substitution atoms and Li insertion in order to achieve a lower enthalpy and a more stable clathrate compound.…”
Section: Hybrid Carbon-boron Clathratesmentioning
confidence: 99%
“…Several energetically competitive structures, however, exist for each clathrate type. These authors concluded that B substitution stabilizes the cage structure and lowers substantially the energy cost for inserting Li atoms into the clathrate cages to about -2eV/Li at 1 atom pressure [21]. In addition, all five carbon clathrates display a semiconducting electronic structure.…”
Section: Hybrid Carbon-boron Clathratesmentioning
confidence: 99%